2021
DOI: 10.21037/tlcr-20-1277
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 detection on circulating tumor-derived extracellular vesicles (T-EVs) from patients with lung cancer

Abstract: Background: Recent breakthroughs in therapies with immune checkpoint inhibitors (ICIs) have revolutionized the treatment of lung cancer. However, only 15-25% of patients respond to the ICIs therapy, and methods to identify those responsive patients are currently a hot research topic. PD-L1 expression measured on tumor tissues using immunohistochemistry (IHC) was approved as one of the companion diagnostic methods, but it is invasive and cannot be used to monitor dynamic changes in PD-L1 expression during treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 42 publications
0
21
2
Order By: Relevance
“…Digital assays have demonstrated utility as a platform for the ultrasensitive detection of proteins 10,37,48 and nucleic acids, 49,50 as well as the analysis of single cells 51,52 and single exosomes. [53][54][55][56]104 dELISA has been commercialized by Quanterix (Fig. 3c) and has found utility in several clinical applications, including traumatic brain injury and cancer diagnostics.…”
Section: Using Micro/nano Devices To Overcome the Limits Of Binding A...mentioning
confidence: 99%
“…Digital assays have demonstrated utility as a platform for the ultrasensitive detection of proteins 10,37,48 and nucleic acids, 49,50 as well as the analysis of single cells 51,52 and single exosomes. [53][54][55][56]104 dELISA has been commercialized by Quanterix (Fig. 3c) and has found utility in several clinical applications, including traumatic brain injury and cancer diagnostics.…”
Section: Using Micro/nano Devices To Overcome the Limits Of Binding A...mentioning
confidence: 99%
“…In a mouse model of melanoma that closely mimics human cancer, the injection of PDL-1-coated exosomes promoted tumour growth and reduced the number of T cells and other immune cells in and around the tumour ( Figure 1 ) [ 162 , 173 , 189 , 190 , 191 , 192 ]. In addition, exosomes carrying PD-L1 have been identified in blood samples of patients with a history of breast cancer, melanoma, or lung cancer who had received treatments for their respective diseases [ 193 , 194 , 195 ].…”
Section: Ev-mediated Immune Escape Of Cancer Cellsmentioning
confidence: 99%
“…Melanoma elicits a particularly strong immune response, and multiple immune checkpoint inhibitors have been approved by the US Food and Drug Administration for the treatment of melanoma [ 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ]. Interestingly, based on PD-L1 levels in exosomes, patients who are most likely to respond to checkpoint inhibitors can be identified and the response to these drugs can be evaluated [ 162 , 194 , 196 , 197 , 198 , 199 ]. For example, compared to patients with high exosomal PD-L1 levels before treatment, those with lower levels responded remarkably better to treatments with the checkpoint inhibitor pembrolizumab (Keytruda), which can block PD-1, the immune cell binding partner of PD-L1 [ 185 , 196 , 198 , 200 , 201 , 202 , 203 , 204 , 205 ].…”
Section: Ev-mediated Immune Escape Of Cancer Cellsmentioning
confidence: 99%
“…EVs collected from saliva may be useful for the diagnosis of lung cancer [ 192 , 193 , 194 ]. It has been reported that the contents of EVs collected from serum, such as miR-200, lipocalin-2 [ 86 ], miR-505-5p [ 91 ], ubiquitin C-terminal hydrolase-L1 (UCHL1) [ 88 ], cell-free DNA [ 82 , 83 ], and proteins [ 195 , 196 , 197 , 198 , 199 ], are useful for the diagnosis of lung cancer. MiR-193a-5p, and miR-551b-5p have been suggested as biomarkers of malignant pleural mesothelioma.…”
Section: Potential Of Evs For Liquid Biopsymentioning
confidence: 99%